2016
DOI: 10.1163/15691624-12341310
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Realities: The Changing Life Worlds of Actors

Abstract: This is an empirical phenomenological interview study into the experiences of professional actors as they create and perform roles for the stage. Prior research was inadequate for capturing actors’ changing life worlds over time. Analyzing the interviews using the descriptive phenomenological method yielded general structural descriptions and pointed to the relevance of Schütz’s description of multiple realities. Being cast in a role changes the pace and goals of actors’ everyday worlds and leads the actors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The author conducted four narrative, phenomenological interviews with professional actors who appeared in featured roles on Broadway and off-Broadway in New York. Findings were reported in two previous papers (Doyle, 2013;2016). Some unpublished material from those interviews will also be included in the review.…”
Section: Phasesmentioning
confidence: 99%
See 4 more Smart Citations
“…The author conducted four narrative, phenomenological interviews with professional actors who appeared in featured roles on Broadway and off-Broadway in New York. Findings were reported in two previous papers (Doyle, 2013;2016). Some unpublished material from those interviews will also be included in the review.…”
Section: Phasesmentioning
confidence: 99%
“…In performance, the musician is in a face-to-face relationship both with the fellow players and the audience. Doyle (2016) concluded that the life worlds of actors can be illuminated by one of Schütz's best known contributions, the phenomenological concept of multiple realities.…”
Section: Forms Of Sociality: the Work Of Alfred Schützmentioning
confidence: 99%
See 3 more Smart Citations